2018
DOI: 10.3390/su10030752
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation as an Enabler for Advanced Services in the Sanitation Sector

Abstract: People in Base of the Pyramid markets still face difficulties when it comes to sanitation. Container-based Sanitation (CBS) services represent a promising advanced sanitation service. Despite the observed outcomes of CBS services, organizations face obstacles when providing these services. To overcome these obstacles, digital transformations of these services are being carried out. We rely on multiple case studies to understand these digital transformations. Our findings highlight (1) the challenges these case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Therefore, based on DT, manufacturing enterprises can promote PDI and meet personalized needs. In the sanitation sector, the literature also found that DT can enable advanced service [36]. Based on the above, the following hypothesis can be given:…”
Section: Digital Transformation and Innovation Performancementioning
confidence: 94%
“…Therefore, based on DT, manufacturing enterprises can promote PDI and meet personalized needs. In the sanitation sector, the literature also found that DT can enable advanced service [36]. Based on the above, the following hypothesis can be given:…”
Section: Digital Transformation and Innovation Performancementioning
confidence: 94%
“…The study shows how digital technologies help overcome the drawback of usage-focused business models in adopting the circular economy. In addition, Jennings Saul and Gebauer [58] use multiple case studies to provide an understanding of the challenges that organizations face when engaging in digital transformation, and how organizations can develop individual digital transformation pathways, which provide a framework for digital transformations with specific focus on Bottom of the Pyramid markets.…”
Section: Introduction To the Special Issue Contributionsmentioning
confidence: 99%
“…Besides Jennings Saul and Gebauer [58], who discuss digital transformation in relation to innovative service offers, Lafuente et al [59] employ fuzzy set analysis (qualitative comparative analysis) to evaluate how the development of sustainable and traditional product innovation strategies is conditioned by the learning capabilities and entrepreneurial orientation of the business. Knowledge intensive business services (KIBS) firms are known to leverage the knowledge-based and customer orientations that characterize their business model in order to compensate for the lack of important organizational characteristics.…”
Section: Introduction To the Special Issue Contributionsmentioning
confidence: 99%
“…This, indeed, is accompanied by another form of thickness variation. Saul and Gebauer [14] studied product failure due to temperature and pressure conditions during longitudinal and transverse stretching processes. Zucker, et al [15] proposed conditions to correct the edge crater condition as a cause of film deformation.…”
Section: Plastic Film Industrymentioning
confidence: 99%
“…In the production of film, customized production systems are being replaced with multi-product small quantity production systems. In addition, as data transformation and modification are easy, and variant production systems continue to grow, the value of services to customers can move closer to the realm of production [14]. Therefore, film production under digital manufacturing means that it can bring new paradigms to the traditional manufacturing market through the reduction of investment costs and management risks and the alleviation of entry barriers.…”
Section: Sustainability On Manufacturingmentioning
confidence: 99%